2015
DOI: 10.1158/1535-7163.mct-14-0836
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin Has ATPase Activity, Which Mediates Its Antiangiogenic and Antitumor Activities

Abstract: Endostatin is an endogenous angiogenesis inhibitor with broad-spectrum antitumor activities. Although the molecular mechanisms of endostatin have been extensively explored, the intrinsic biochemical characteristics of endostatin are not completely understood. Here, we revealed for the first time that endostatin embedded novel ATPase activity. Moreover, mutagenesis study showed that the ATPase activity of endostatin mutants positively correlated with effects on endothelial cell activities and tumor growth. E-M,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…When these treatments are compared at the time of sacrifice at the end of the study, there is a clear reduction on the presence of lung metastases (Figure 6). Comparisons to endostatin, known to prevent metastases in the mouse [63,64] and now known to possess ATPase activity [65] consistent with an action in the NM23:P2Y 1 R pathway, are encouraging offering both a comparative benefit as well as suggesting a mechanistic role for endostatin consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…When these treatments are compared at the time of sacrifice at the end of the study, there is a clear reduction on the presence of lung metastases (Figure 6). Comparisons to endostatin, known to prevent metastases in the mouse [63,64] and now known to possess ATPase activity [65] consistent with an action in the NM23:P2Y 1 R pathway, are encouraging offering both a comparative benefit as well as suggesting a mechanistic role for endostatin consistent with our hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…Although not extensively studied, the results of in vivo experiments support endostatin’s anti-lymphangiogenic role based on its inhibition of bFGF-induced lymphangiogenesis [165]. Endostatin has recently been found to have intrinsic ATPase activity in vivo , which mediates its anti-angiogenic and anti-tumoral activities by further inhibiting endothelial cell proliferation, migration, tube formation, and adhesion [166]. …”
Section: In Vitro and In Vivo Models Of Endostatin’s Role In Angiomentioning
confidence: 99%
“…exerts a wide-ranging antitumour effect via suppression of pathological angiogenesis and suppression of tumours proliferation and metastasis. [12][13][14] The rhES is a novel antiangiogenic agent that is derived from endostatin by adding nine amino acids to the peptide chain N-terminal of endostatin, with a longer half-life period, heightened purity, bioactivity and stability. 15,16 It has been revealed that rhES improved antitumour validity when combined with cytotoxic drugs in Lewis lung carcinoma, 17 and rhES enhanced antitumour efficacy when combined with conventional chemotherapy.…”
Section: Ta B L E 1 Comparison Of Adverse Effects Between Different Gmentioning
confidence: 99%